2009
DOI: 10.1111/j.1365-2044.2009.06071.x
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia after general anaesthesia: a case report

Abstract: SummaryAlthough anaesthetic drugs are included among the aetiological factors of anosmia, limited reports exist of anosmia induced by general anaesthesia. We present the case of a 60-year-old female patient with a 3-month history of altered smell and taste immediately after recovery from general anaesthesia for a urological operation. The anaesthetic drugs used were fentanyl, propofol and sevoflurane. Clinical examination and a computed tomography brain scan did not reveal any pathology. Psychophysical testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…This article is in line with some recently published work [7] and contributes to the general discussion about this complication [8]. Most specialized smell and taste clinics have been confronted with cases of patients claiming smell or taste loss after general anesthesia.…”
supporting
confidence: 83%
“…This article is in line with some recently published work [7] and contributes to the general discussion about this complication [8]. Most specialized smell and taste clinics have been confronted with cases of patients claiming smell or taste loss after general anesthesia.…”
supporting
confidence: 83%
“…In addition to the three main causes of olfactory dysfunction, surgical procedures [46] (both sinonasal surgeries [47] and other types of surgery [48]) can affect olfactory function. Some of these cases are likely due to side-effects of the drugs used for general anesthesia [49-51]. Other drugs can also have side-effects on olfactory function [52-55].…”
Section: Introductionmentioning
confidence: 99%
“…Konstantinidis et al reported a 60 year old woman who had a 3-month history of altered smell after general anesthesia with propofol and sevoflurane for a urologic operation [9]. In their report, the authors offered scientific support for their hypotheses linking inhalational and intravenous anesthetics to dysosmia (a distorted identification of smell).…”
Section: Discussionmentioning
confidence: 98%
“…They cited clinical studies that have shown that sevoflurane and propofol affect γ-aminobutyric acid (GABA) receptor ligand binding [10]. Given that GABA is the main inhibitory neurotransmitter of the brain involved in many areas, including synapses in olfactory bulbs, it is conceivable that such anesthetic agents may affect the olfactory system at any level of the pathway [9,11]. In fact, decreased brain GABA has been seen in patients with phantageusia and phantosmia (olfactory and gustatory hallucination, respectively), with clinical improvement after an increase in brain GABA levels by GABAergic drugs [11].…”
Section: Discussionmentioning
confidence: 99%